Analysis of The Use Of SIASN in The Personnel and Human Resources Development Agency (BKPSDM) in Palangkaraya City Using The Hot Fit Approach - Mita Ashary; Ardieansyah Ardieansyah (Journal of Politica Governo, 2025)
This study aims to examine how SIASN is utilized at the BKPSDM of Palangkaraya City. Based on the researcher's observations, the use of SIASN has not yet been explored in previous studies, making it the novelty of this research. The ASN Index Score (IP ASN) of Palangkaraya City ranked 17th with a "very low" category as of February 28, 2024, according to the official website of the ASN Data Rejuvenation Index for Region VII. This prompted the researcher to explore further the use of SIASN and its challenges in order to find solutions that could benefit BKPSDM Palangkaraya City. This research adopts a qualitative approach and uses the NVivo 12 Plus application for data processing. The findings show that the implementation of SIASN at BKPSDM Palangkaraya City has been carried out properly based on the HOT Fit framework, which includes human, organizational, technological, and benefit aspects. However, there are still several aspects that need improvement, such as the intensity of system usage, user satisfaction levels, and the quality of services provided. The main challenges include age differences that affect the ability to operate the technology, as well as delays in data processing when the system is used in large volumes, especially towards the end of the year. On the other hand, factors such as system quality, information quality, organizational structure and environment, as well as the benefits produced, have functioned well and should continue to be maintained and improved.